Application of Promotion Mix for KH Laundry - Micel Thai; Suyono Saputra (ConCEPt - Conference on Community Engagement Project, 2023)
KH Laundry is a shop engaged in laundry services in Batam City. Many people still need to know or recognize the existence of KH Laundry. Besides that, KH Laundry also still applies traditional management systems or less developed techniques, such as not having an Instagram account. While today's technology is developing rapidly, every business must understand making correct and effective marketing strategies to make the business grow and expand. Therefore, the method that will be applied to KH Laundry is to use the type of promotion mix, which can also be referred to as the promotion mix. Data collection uses observation by visiting the business and conducting interviews via Whatsapp. The conclusion from the research is the importance of improving marketing strategies through an easy-to-use technology platform to increase company sales so that they can compete with other businesses.